Examining material constitutive response under dynamic compression and large plastic strains using in situ imaging of hole closure. (March 2021) - Lind, Jonathan; Nelms, Matthew D.; Robinson, Andrew K.; Kumar, Mukul; Barton, Nathan R.
Graphical abstract: Abstract: For understanding material performance under dynamic loading, there is significant interest in the strain rate dependence of material response and in the degree to which high-rate response depends on initial material state. Experimental tests at high strain rates (> 10 3 / s ) often use measurement of shape change to infer flow strength behavior. Given stress and strain heterogeneities, inferences about flow strength behavior from those observations are facilitated by comparisons with advanced simulations. A new plate impact-based experimental test is described, consisting of in situ X-ray imaging to observe the closure of a cylindrical hole during the passage of a pressure pulse of controlled amplitude and duration. With the goal of providing unique data regarding plastic response at high strain rates, the closure of the hole is measured through time using multi-frame imaging. A first set of experiments on copper examines the role of starting microstructure on material flow behavior. The experimental observations are compared with predictions from direct numerical simulations using the Preston-Tonks-Wallace (PTW) and the Mechanical Threshold Stress (MTS) flow strength models. The quantitative utility of the overall approach is demonstrated in that the results provide information about MTS model parameters associated with high-rate hardening behavior, with the parameters having been unconstrained by quasi-static experimental data.